2013
DOI: 10.1248/cpb.c13-00221
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and <i>in Vitro</i> Antifungal Activities of New 2-Aryl-6,7-methylenedioxy-3,4-dihydroisoquinolin-2-ium Bromides

Abstract: 2-Aryl-3,4-dihydroisoquinolin-2-iums might be considered as a class of simple analogues of natural quaternary benzo[c]phenanthridine alkaloids. In this paper, 26 new 2-aryl-6,7-methylenedioxy-3,4-dihydroisoquinolin-2-ium bromides with various substituents in N-aromatic ring were synthesized from commercially available 1,3-benzodioxole in good to excellent yields. All the compounds were elucidated by MS, high resolution (HR)-MS, IR, 1 H-and 13 C-NMR analysis, and evaluated for antifungal activities in vitro aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…In addition, our study also found that the C=N + moiety in ADHIQs is a determinant for their bioactivities including antifungal properties 5 , 9 , and the antifungal activity of ADHIQs is closely related to the electron density distribution in its conjugated system, especially in the C=N + bond 9 13 . The substitution patterns of the two aryl-rings can significantly impact the activity.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, our study also found that the C=N + moiety in ADHIQs is a determinant for their bioactivities including antifungal properties 5 , 9 , and the antifungal activity of ADHIQs is closely related to the electron density distribution in its conjugated system, especially in the C=N + bond 9 13 . The substitution patterns of the two aryl-rings can significantly impact the activity.…”
Section: Introductionsupporting
confidence: 59%
“…1 ) can be considered as a class of structurally simple analogues of sanguinarine (SA) or chelerythrine (CH) with diverse biological effects, two quaternary benzo[c]phenanthridine alkaloids (QBAs). Our previous study proved that like SA and CH 5 8 , ADHIQs generally possessed excellently antifungal 9 13 , acaricidal 14 , 15 and anticancer activities 5 , 16 , and also showed high safety to plant growth 17 , 18 . These results show that ADHIQs are of great potential as new or secondary lead compounds to develop QBA-like antifungal agents.…”
Section: Introductionmentioning
confidence: 96%
“…45) Aromatic aldehyde 1 was obtained from sesamol by the reaction of Vilsmeier-Haack formylation in 11% yield. 46) 1,3-Benzodioxole reacted with paraformaldehyde in a concentrated HCl solution to provide 2, 47) and followed by treatment with bromine in glacial acetic acid to yield 4 in 92% yield. 48) Compounds 2 and 4 were oxidized by dimethylsulphoxide oxidation in the presence of NaHCO 3 to yield intermediates 3 and 5, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Tebuconazole (≥ 99.1%), a commercial fungicide, was used as the positive control. Compound 7a was regarded as the reference compound.…”
Section: Resultsmentioning
confidence: 99%